Trangression as a sign of stability. Casus of Michael Czajkowski – Sadyk Pasza - Fabianowski, Andrzej (Biografie nieoczywiste: Przełom, kryzys, transgresja w perspektywie interdyscyplinarnej, 2018)
Michał Czajkowski was a nineteenth-century writer - a representative of the so- called school of the Ukrainian romanticism, politician and military. He took part in the uprising in November, went to emigrate, where on the recommendation of Fr. Adam J. Czartoryski undertook to build a „diplomatic consulate” in Istanbul. In Turkey he vigorously worked for the war against Russia. He converted to Islam, adopting the name Mehmet Sadyk Pasha. As a Turkish general, he built his own military formation - Otomans Division, which he led during the Crimean War. In 1855 Adam Mickiewicz visited the Cossack camp, inspiring Sadyk to create the Jewish Legion, which would have might, in the poet’s view, an impact on the course of history. Offended to the margins of political life in Turkey, he accepted a Tsarist amnesty, went to Orthodoxy, and settled in Volhynia. He died of suicide. His life is an example of variability, always subordinate to the chief idea – the restitution of the gooseberry, which would become a force capable of rebuilding an independent, multinational Polish Republic.